Vestibulo-Ocular Reflex Stabilization after Vestibular Schwannoma Surgery: A Story Told by Saccades - Batuecas-Caletrio, Angel; Rey-Martinez, Jorge; Trinidad-Ruiz, Gabriel; Matiño-Soler, Eusebi; Cruz-Ruiz, Santiago Santa; Muñoz-Herrera, Angel; Perez-Fernandez, Nicolas (Frontiers in Neurology, 2017)
Objective. To evaluate vestibular compensation via measurement of the vestibulo-ocular reflex (VOR) following vestibular schwannoma surgery, and its relationship with changes in saccades strategy after surgery. Patients. 36 consecutive patients with vestibular schwannomas, without midbrain compression, who underwent surgical resection. Patients were recruited from University Hospital of Salamanca, Spain. Methods. We assessed the age, sex, tumour size, degree of canalicular weakness and pre-operative video head impulse test (Gain and saccade organization measured with PR score). Gain and saccade organization were compared with post –operative values at discharge and also at 1, 3 and 6 months. PR scores are a measure of the scatter of refixation saccades. Results: Patients with normal pre-operative caloric function had higher PR scores (saccades were scattered) following surgery compared to patients with significant pre-operative canal paresis (P<0.05). VOR gain and the presence of covert/overt saccades pre-operatively did not influence the PR score (P>0.05), but a group of patients with very low VOR gain (<0.45) and covert/overt saccades before surgery had lower PR scores after surgery. The differences after six months were not significant. Conclusions: Patients with more severe vestibular dysfunction before vestibular schwannoma surgery show significantly faster vestibular compensation following surgery, manifested by changes in VOR gain and PR score. The scatter of compensatory saccades (as measured by the PR score) may be a surrogate early marker of clinical recovery, given its relationship to the Dizziness Handicap Inventory.